Headache Attributed to SARS-CoV-2 Infection or COVID-19 Related Headache—Not Migraine-like Problem-Original Research - Aleksandra Kacprzak (MDPI AG, 2021)
Background: Many studies have confirmed headache as one of the most common COVID-19-related neurological symptoms. There are some reports concerning migraine attacks during SARS-CoV-2 infection with an unusual course of migraine attack. Our aim was to recognize and characterize accurately the features of headaches accompanying this disease. Methods: Research based on questionnaire study gathered 100 randomly chosen medical healthcare employees who experienced symptoms associated with COVID-19 disease, 96 with confirmed COVID-19 (positive SARS-CoV-2 PCR laboratory test or positive rapid COVID-19 antigen test). Conclusion: Headaches reported in the study did not fulfill criteria for migraine with/without aura, tension-type headache according to ICHD-3.